2022
DOI: 10.23887/jpbi.v10i1.796
|View full text |Cite
|
Sign up to set email alerts
|

The Deixis Used in the Song Lyrics Performed by the Most Popular Boy Group BTS

Abstract: This study aimed to investigate the deixis types used in BTS’ English song lyrics and find out the dominant type which was frequently used. Song lyrics were chosen as the focus of this study since they involved the singers’ feelings and emotions presented by some expressions related to human thoughts, ideas, and opinions. The theories from Levinson (1983) and Yule (1996) and were used to analyze the data. Descriptive qualitative in the form of document analysis was implemented in this study. The results found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It could be said from the above literature review that although a lot has been written on the use of deixis (see Kusumanigtyas & Halimah, 2020;Amin & Jukil, 2019;Indawa & Utami, 2022;Herdiyanti, 2020;Fani, 2020;Aryawan, Budasi & Ramendra, 2022;Nisa, Asi & Sari, 2020;Nurfadilla, 2023), no work has investigated on person deixis as shifts in authority in academic writing which is the focus of this paper. This review therefore gives this researcher a starting point and a way forward.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It could be said from the above literature review that although a lot has been written on the use of deixis (see Kusumanigtyas & Halimah, 2020;Amin & Jukil, 2019;Indawa & Utami, 2022;Herdiyanti, 2020;Fani, 2020;Aryawan, Budasi & Ramendra, 2022;Nisa, Asi & Sari, 2020;Nurfadilla, 2023), no work has investigated on person deixis as shifts in authority in academic writing which is the focus of this paper. This review therefore gives this researcher a starting point and a way forward.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a lot of previous studies have been found in papers, most of them focus on song lyrics (Aryawan et al, 2022;Rokhmah & Santoso, 2022, Salamudin & Efransyah, 2021Sinaga et al, 2020), film (Dion Ari Saputra et al, 2022;Hidayat et al, 2021), and talk show (Putri et al, 2022), to mention a few. Although deixis was also studied in talk show, the data were not taken from Ellen Guneres.…”
Section: Introductionmentioning
confidence: 99%